Krishna
0

Step 1:  Note down the given equation

             NOTE: \cos(60\degree + 30\degree) = \cos 60\degree \cos 30\degree - \sin 60\degree \sin 30\degree


Step 2: Take L.H.S side of the equation and simplify

              EXAMPLE:   \cos(60\degree + 30\degree)                          

                                   =   \cos(90\degree)

                                   = 0


Step 3: Take R.H.S side of the equation and simplify

                 \cos 60\degree \cos 30\degree - \sin 60\degree \sin 30\degree

                    = \frac{1}{2}\frac{\sqrt{3}}{2} - \frac{\sqrt{3}}{2} \frac{1}{2}

                    = \frac{\sqrt{3}}{4} - \frac{\sqrt{3}}{4}

                    = 0


Step 4:  Conclude that the given equation in right

              EXPLANATION:  From Step 1 and Step 2

                                          we can conclude that L.H.S = R.H.S

                                              

             \cos(60\degree + 30\degree) = \cos 60\degree \cos 30\degree - \sin 60\degree \sin 30\degree

                   is true